Penilaian Green Building pada Gedung Laboratorium Terpadu II Institut Teknologi Kalimantan - Choirunisa, Yulia; Sari, Oryza Lhara; Anindyta, Imma Sofi (Indonesian Society of Applied Science, 2025)
Efforts are essential to reduce emissions and environmental damage from construction activities, such as applying green concepts throughout the construction process. Institut Teknologi Kalimantan (ITK) is a sustainable development initiative in East Borneo that adopts these green concepts. Specifically, the Gedung Laboratorium Terpadu II at ITK was planned as a green building but hadn't undergone an assessment. This study assessed the building using the Greenship New Building Version 1.2 tool, revealing that it scored 25 points (24.75%), falling short of green building status. Recommendations for improvement included increasing vegetation, implementing energy and water efficiency measures, sourcing alternative water supplies, enhancing lighting systems, and improving waste treatment. These changes could elevate the building's green status to gold, with a 59.41% score.